2011
DOI: 10.1101/lm.2034711
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal attentional engagement rescues mice from age-related cognitive declines and cognitive inflexibility

Abstract: Learning, attentional, and perseverative deficits are characteristic of cognitive aging. In this study, genetically diverse CD-1 mice underwent longitudinal training in a task asserted to tax working memory capacity and its dependence on selective attention. Beginning at 3 mo of age, animals were trained for 12 d to perform in a dual radial-arm maze task that required the mice to remember and operate on two sets of overlapping guidance (spatial) cues. As previously reported, this training resulted in an immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 50 publications
4
37
1
Order By: Relevance
“…Experiment 3: Effect of working memory training on cognitive performance and D1 sensitivity It has been reported that the imposition of a working memory training regimen with a high demand on selective attention can promote an increase in the general cognitive performance of mice Matzel et al 2011). Here we ascertained if working memory training targeted the same dopaminergic signaling mechanisms (D1R-containing neurons) that underlie innate cognitive abilities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiment 3: Effect of working memory training on cognitive performance and D1 sensitivity It has been reported that the imposition of a working memory training regimen with a high demand on selective attention can promote an increase in the general cognitive performance of mice Matzel et al 2011). Here we ascertained if working memory training targeted the same dopaminergic signaling mechanisms (D1R-containing neurons) that underlie innate cognitive abilities.…”
Section: Resultsmentioning
confidence: 99%
“…Since working memory training required animals to actively maintain a memory of locations in the face of interfering external stimuli, that taxation (and its use of the D1R) may have increased the sensitivity of D1R-containing neurons. It is notable in this regard that implementation of a similar working memory training regimen also resulted in improved performance on specific tests of selective attention Matzel and Kolata 2010;Matzel et al 2011).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in the largest human brain-training study of its kind on over 11,400 participants, Owen et al (2010) showed that, whereas a subject's performance on a trained CGT improved over a six-week period, their performance did not transfer to similar untrained CGTs. In animals, Matzel et al (2011) found that general cognitive decline in aging mice was reduced by life-long working memory exercises (navigation of 3D mazes). Most cognitive tasks provided to rats and dogs have been spatial (i.e., mazes and obstacle courses); therefore, it is difficult to determine whether cognitive performance in these cases is enhanced by "using the body" or "using the brain", or indeed both.…”
Section: Cognitive Enrichment Attempts In Captive Settingsmentioning
confidence: 99%